Identification of Profound Metabolic Alterations in Human Dendritic Cells by Progesterone Through Integrated Bioinformatics Analysis - Zhang, Sainan; Liu, Su; Hong, Ling; Wang, Xiaohui; Diao, Lianghui; Cai, Songchen; Yin, Tailang; Zeng, Yong (Frontiers in Immunology, 2021)
Maintaining the homeostasis of the decidual immune microenvironment at the maternal-fetal interface is essential for reproductive success. Dendritic cells (DCs) are the professional antigen-presenting cells and dominate this balance of immunogenicity and tolerance. Progesterone (P4) is highlighted as the “hormone of pregnancy” in most eutherian mammals because of its regulatory role in immune-endocrine behavior during pregnancy. Recent studies have shown that P4 is associated with the differentiation and function of DCs, however, the underlying mechanisms remain unidentified. In addition, while progress in the field of immunometabolism has highlighted the intimate connections between the metabolism phenotype and the immunogenic or tolerogenic fate of DCs, whether P4 can affect DCs metabolism and thus exert a functional manipulation has not yet been explored. In this study, we acquired human peripheral blood monocyte-derived DCs and conducted RNA sequencing (RNA-seq) on immature DCs (iDCs), P4-treated DCs (pDCs), and mature DCs (mDCs), aiming to comprehensively assess the effects of P4 on DCs. Our results showed pDCs performed a distinct differentially expressed genes (DEGs) profile compared with iDCs or mDCs. Further functional enrichment and weighted gene co-expression network (WGCNA) analysis found that these DEGs were related not only to the cellular components but also to the significant metabolic activities, including mitochondrial oxidative phosphorylation (OXPHOS) and fatty acid metabolism. In addition, these changes may be involved in the activation of various signaling pathways of PI3K/Akt/mTOR, AMPK/PGC1-, and PPAR-. In summary, our work suggested that P4 induced profound metabolic alterations of mitochondrial OXPHOS and fatty acid metabolism in DCs. Our findings may provide new insights into the role of P4 in DCs.